Magnetic Resonance Imaging of Experimental Tendonitis in Sheep - Hurtig, M. B.; Stewart, W. A.; Trout, D. R.; Dobson, H.; Bahr, R. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
Experimental tendonitis in sheep is used to demonstrate the advantages of magnetic resonance imaging: three-dimensional imaging ability, high image resolution and the ability to detect alteration in tissue composition that occurs in pathological states.
Keywords: Magnetic resonance imaging; tendonitis; equine